Penyuluhan Literasi Keuangan Digital Pada Perempuan di Desa Wisata Banyumulek, Kabupaten Lombok Barat - Hafizah Awalia; Saipul Hamdi; Arif Nasrullah (Jurnal Ilmiah Pengabdian dan Inovasi, 2022)
Banyumulek is a tourist village which is famous for its pottery crafts and there is a group of women craftsmen who are the pillars of improving the community's economy. Therefore, the service team aims to carry out outreach activities related to digital financial literacy in West Lombok Regency. The implementation of this service is located in Banyumulek Village, Kediri District, West Lombok Regency with the target of female pottery craftsmen and a community of women who use gadgets and use the internet in their daily activities. The result of this service is that there are still many female pottery craftsmen who do not know the risks of using digital financial platforms such as Phishing, Phraming Mobile, Sniffing, Money Mule and Social Engineering. In addition, there are still many who are confused in choosing the right platform to use, so that there is counseling from the Mataram University service team. The community of women pottery craftsmen became aware of the platforms and information they had to choose and sort out in order to avoid misuse of personal data as well as security and convenience in using social media.